Biosynthesis and Transport of Nucleotide Sugars for Plant Hemicellulose - Zhang, Wenjuan; Qin, Wenqi; Li, Huiling; Wu, Ai-min (Frontiers in Plant Science, 2021)
Hemicellulose is entangled with cellulose through hydrogen bonds and meanwhile acts as a bridge for the deposition of lignin monomer in the secondary wall. Therefore, hemicellulose plays a vital role in the utilization of cell wall biomass. Many advances in hemicellulose research have recently been made, and a large number of genes and their functions have been identified and verified. However, due to the diversity and complexity of hemicellulose, the biosynthesis and regulatory mechanisms are yet unknown. In this review, we summarized the types of plant hemicellulose, hemicellulose-specific nucleotide sugar substrates, key transporters, and biosynthesis pathways. This review will contribute to a better understanding of substrate-level regulation of hemicellulose synthesis.